Accelerating Halal Certification: Al-Siyasah Shar’iyyah Analysis of Local Government Strategies and Systemic Challenges for Madura’s MSMEs - Ahmad Musadad; Taufiqur Rahman; Baihaqi, Baihaqi; Mustaniroh, Mustaniroh; Tri Pujiati (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2025)
Indonesia’s mandatory halal certification deadline of 17 October 2026 poses a pressing challenge for Micro, Small, and Medium Enterprises (MSMEs) for Sharia-compliant legal assurance to maintain consumer trust and enhance market competitiveness. This study examines the strategic role of local governments in accelerating halal certification for MSMEs using Siyasah Shar’iyyah approach with the principle of Tasharruf al-imām ‘alā al-Ra‘iyyah manūṭun bi al-Maṣlaḥah. This study used interviews and policy analysis for qualitative analysis. The qualitative multi-case approach examines halal certification acceleration across Madura's four regencies (Bangkalan, Sampang, Pamekasan, and Sumenep) through interviews with key stakeholders, participatory observation, and policy document analysis. The findings demonstrate that local governments are proactively advancing halal certification through targeted approaches. These include deploying Islamic religious counsellors, participating in national certification initiatives, and providing free certification programs to facilitate MSME compliance with halal requirements. Despite proactive efforts, the study identifies three persistent challenges hindering halal certification acceleration, including fragmented coordination between implementing institutions, unequal progress across regions, and insufficient local testing infrastructure, particularly for meat and animal-derived products. To address these systemic barriers, the study proposes mobile halal laboratories to expand testing coverage, digital platforms for accessibility, and Islamic boarding schools for continuous training. The findings bridge critical theory and practice, offering scalable approaches to enhance regulatory compliance and equitable halal certification access for MSMEs.